Отцовская куртка: рассказы о войне / Валентина Осеева - Осеева Валентина Александровна (Омега, 2018)
Экземпляры: ф.7 (20241015) / Инвентарный номер: 64619 / Цена: 100.00 / Авт.знак: О-72 / ГРНТИ: 17.82.93 /